GOVERNMENTAL ORGANIZATIONS AND THEIR ROLE IN MISSIONS OF INTERNATIONAL COOPERATION OF UKRAINE LIBRARY - Lapska, Olha O . (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2016)
The article focuses on the role of civil society organizations in representing the interests of various groups and ensure the relationship of state and society. The analysis of Ukrainian Library Association, which promotes international cooperation in all areas of librarianship. Determined the importance of a public organization to improve international cooperation in the field of librarianship Ukraine.